Analysis of the diagnostic role of fibrin-related markers in perioperative venous thromboembolism - Wei, Min; Pan, Yongjiang; Qin, Zheng; Chen, Lihua; Zhao, Liping; Zhong, Debin (Frontiers in Surgery, 2025)
ObjectivesTo investigate the diagnostic role of fibrin-related markers in the perioperative venous thromboembolism (VTE).MethodsA total of 100 high-risk perioperative patients, identified using the Caprini thrombosis risk assessment model [46 with deep vein thrombosis (DVT) and 54 with pulmonary embolism (PE)], were included as study subjects. Additionally, 50 healthy volunteers undergoing medical checkups during the same period served as controls. The levels of D-dimer, fibrin monomer (FM) and fibrin degradation products (FDP) were compared between patients and the control group across different time points. Additionally, the influence of various factors on these biomarkers was assessed. Furthermore, the diagnostic value of fibrin-related markers in perioperative VTE among surgical patients was analyzed.ResultsThe levels of D-dimer, FM and FDP on postoperative days 1, 3 and 7 were significantly lower than those on the day before surgery, showing a sequential decline over the postoperative period (p < 0.05). The levels of these three markers were significantly higher in the PE group than in the DVT group, and higher in the DVT group than in the control group (p < 0.05). No significant differences were observed in these markers based on gender, age or disease conditions (p > 0.05). Additionally, ROC curve analysis indicated that FM detection alone had good diagnostic value, with an AUC of 0.835 and a sensitivity of 88.34%. And joint detection (D-dimer, FM, FDP) provided superior diagnostic performance.ConclusionThe combination of D-dimer, FM, FDP and Caprini scores may enhance the diagnostic accuracy of VTE in the perioperative period. If all four indicators are not readily available, monitoring FM levels alone can provide valuable diagnostic insight.